Political Loyalty in Modern Islamic Thought: Multiplicity and Implications - Abdessamad Belhaj (Islamic Studies Review, 2026)
This paper argues that mainstream Muslim schools of thought support multiple loyalties, including country, ethnicity, tribe, and religion. First, we provide a summary of the major positions held by various Muslim schools of thought regarding the concept of al-walāʾ wa-l-barāʾ (loyalty and disavowal). The article then addresses the implications of these loyalties in contemporary Muslim politics. We focus on how these discourses on loyalty construct enemies of Islam and Muslims. Finally, we show how various political factors impact Muslim allegiances and how commitment to Islam can complement and be consistent with civic responsibility in secular and pluralistic democracies, particularly Western societies.